PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAKAN CATCALLING DI PLATFORM MEDIA SOSIAL SEBAGAI BENTUK KASUS KEJAHATAN SEKSUAL - Mega Fitri Andriyani; Burham Pranawa; Nanik Sutarni (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
The transformation of sexual harassment from physical public spaces to cyberspace has given rise to a new form of crime known as digital catcalling. This phenomenon demonstrates the complexity of the law, which has not fully responded to the characteristics of gender-based crimes in the virtual world. This study aims to analyze the forms of legal protection for victims of catcalling on social media and examine the obstacles and government efforts in its implementation. The research method used a normative-descriptive approach with qualitative analysis. The results indicate that although regulations such as the TPKS Law, the Pornography Law, and the ITE Law exist that can be used to prosecute perpetrators, legal protection for victims remains ineffective due to the lack of specific norms explicitly governing digital catcalling. Systemic integration between regulations and a gender- and technology-based approach is needed to strengthen victim protection